(untitled) (Praxis Educativa, 2022)
The writing of the postgraduate dissertation implies for the candidates a process of gradual incorporation as valid interlocutors within their disciplinary academic field. In this context, the writing of the thesis project constitutes a relevant experience for novice researchers. This article analyses, from an autoethnographic perspective, our experiences as doctoral students in Social and Human Sciences based on the writing of each other’s thesis projects. To achieve this goal, we created two autobiographical narrative records that were analyzed based on the ideas of academic literacy, intellectual affiliation and agency. The research findings indicate that the formal and institutional logics, the interaction with experts and the preparation of successive drafts have significantly conditioned the writing of our thesis projects and the construction of our identity as beginning researchers.